The Role of Telomeres and Telomerase in Cancer Research - Stewart, Sheila A. (2010)
The fourth AACR Special Conference on The Role of Telomeres and Telomerase in Cancer Research was held February 27–March 2, 2010 in Fort Worth, Texas. The meeting was organized to bring together those interested in the basic molecular mechanisms that govern telomere dynamics and stability with those interested in the clinical implications of telomere dysfunction and the use of telomeres and telomerase as therapeutic targets. The meeting was extremely successful as evidenced by the attendance and quality of the presentations. Indeed, several important themes emerged including 1) the intricate connection between the DNA replication and repair machineries in basic telomere replication and stability; 2) the complex interplay between the telomere-specific shelterin components and DNA repair proteins; 3) the non-telomeric functions of TERT in numerous cell types including stem cells; 4) a growing appreciation for the connection that exists between telomere maintenance deficiency states and diverse conditions such as idiopathic pulmonary fibrosis and hematopoietic malignancies; and 5) the successful progression of agents targeting telomerase directly and immunologically to Phase III clinical trials. Evident at the meeting was the vibrant energy that permeates the telomere field and the important biological and medical findings that it continues to yield.